Arbutin attenuates nephrotoxicity induced by gentamicin - Elnaz Emadi; Mahdi Pouramir; Maryam Ghasemi-Kasman; Farideh Feizi; Sohrab Halalkhor; Ali Akbar Moghadamnia (Mashhad University of Medical Sciences, 2021)
Objective: In this study, the impact of arbutin was examined in a gentamicin (GM)-induced nephrotoxicity model. Materials and Methods: Forty adult male Wistar rats were randomly assigned to five groups including control group; GM group, and three groups of GM+arbutin (25, 50 and 75 mg/kg). One day after the last injection of GM, creatinine, urea, carbonyl, thiobarbituric acid-reacting substance (TBARs), ferric reducing antioxidant power (FRAP) and 8-hydroxyguanosine levels were assessed in serum samples. Left and right kidneys were used for biochemical assays and histological evaluation, respectively. Results: Our data showed that the FRAP level (p<0.05), urea (p<0.001), creatinine (p<0.001), and 8-hydroxyguanosine (p<0.001) levels of serum samples, were increased in GM-treated rats compared to the controls. The serum levels of TBARS (p<0.001) and carbonyl increased in serum and renal tissue (p<0.001) of GM-treated animals. Conversely, arbutin attenuated serum creatinine, urea and 8-hydroxyguanosine, and TBARS (p<0.001). Administration of arbutin significantly decreased carbonyl levels in serum and renal tissue samples (p<0.001). Furthermore, the levels of FRAP increased in the serum (p<0.01) and renal tissue samples (p<0.001) of arbutin-treated animals. Histological staining showed that arbutin significantly inhibits kidney damages. Conclusion: Our data suggest that arbutin attenuates GM-induced nephrotoxicity through its free radicals-scavenging activity.